DESIGN OF A PLANAR UWB ANTENNA WITH BAND REJECTION - FADHEL, YASSER A.; AL-SULAIFANIE, BAYEZ K. (Journal of Duhok University, 2017)
This paper is oriented on the design of a planar Ultra-Wideband (UWB) antenna covering the entire UWB frequency range with band-rejection of (5.18 – 6.10 GHz) to avoid the interference with other existing wireless communication systems like WLAN and WiMAX. The band-rejection has been performed by adding a slit to the circular radiating patch transversely to the direction of current flow with a length tuned to the effective half-wavelength which is opposite to the center of rejected band (5.5 GHz). The length of the added slit has been chosen according to a suggested formula unlike other previous works done by trial and error method. CST software package has been used to simulate the designed antenna. Simulation results have shown that this antenna obeys the UWB requirements with a reduction in its gain at the rejection band. Practical implementation has also been performed and measurements confirm the design and simulation results.